Evaluation of Psychometric Properties of the Farsi Version of the Work-Related Affective Feelings Scale - Roghieh Nooripour; Nahid Hoseininezhad; Parviz Fadakar Gabalou; Davod Fathi (Psychology in Russia: State of Art)
Background. Attention to emotions is growing in workplaces. To address this interest, new psychological instruments have been developed to assess the emotional states of individuals at work. The Work-Related Affective Feelings (WORAF) Scale is a new psychological tool for measuring four main emotions: happiness, anxiety, anger, and dejection at work. Objective. To determine psychometric properties of the Farsi version of the WORAF Scale in Iran. Design. This research employed a cross-sectional research design. The sample consisted of 514 people (250 females and 264 males). We collected data using the Work-Related Affective Feelings Scale, the Job-Related Affective Well-Being Scale, and the Ten-Item Personality Inventory. Confirmatory Factor Analysis was used to check the factorial structure of this scale. The Pearson correlation coefficient and Cronbach’s alpha were analyzed using SPSS version 26 and R software version 4.2. Results. The model fit indices suggested satisfactory fit for the final models as CFI = .907, TLI = .904, NFI = .907, IFI = .907, X²/df = 3.809, RMR = .055, and RMSEA = .079. The Cronbach’s alpha of the scale was .87 and values ranging from .73 to .92 confirmed the reliability of the WORAF. The Pearson correlation analysis revealed a statistically significant relationship between this scale and similar scales, verifying the convergent validity of this scale and similar scales. Conclusion. The findings provide empirical support and introduce the WORAF Scale as a valid and reliable scale translated and validated in Iran. The Farsi version of this scale can measure four major emotions of individuals in Iranian workplaces. This scale can be used by Iranian researchers as well as by organizational practitioners to measure, identify, and improve the emotions employees experience in their workplaces. Considering the large number of employees in the private and public sectors in Iran, this scale can be and useful.